The Strategy of Collecting and Distributing Qur'an Waqf at Trans Studio Bandung Grand Mosque: SWOT Analysis - Muhammad Fauzi Arif; Fahmi Fatwa Rosyadi Satria Hamdani (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2023)
This research aims to determine Al-Quran waqf's funding and distribution strategy at Trans Studio Bandung Grand Mosque. The type of this research is qualitative and uses a descriptive study method. The research approach is SWOT analysis. Data collection techniques used interviews, observation, and documentation. The research results show that Al-Quran waqf's funding and distributing strategy at Masjid Trans Studio Bandung is carried out in two ways: 1) opening a waqf outlet and 2) presenting strategy. The results of the SWOT analysis are Strengths, the existence of a special team that focuses on managing Al-Quran waqf, the potential for Al-Quran waqf is quite large, the geographical location, e-money waqf transactions system, a good network of collaboration partners. Weaknesses include not having an Al-Quran waqf funding raising target, needing a schedule for Al-Quran waqf education, needing more professional human resources, and not optimizing social media to inform the waqf program. The opportunities are to develop in achieving the Al-Quran waqf program optimizing cooperation with external parties. The threats include the existence of Al-Quran waqf institutions that are more experienced and known by the public, and public literacy regarding Al-Quran waqf still needs to improve.